Modified glass fiber material, preparation method thereof and application of modified glass fiber material as demolding cloth

By modifying the surface of the glass fiber with silicone release agent or non-silicon release agent, a modified glass fiber material that is resistant to high temperature of 400℃ was prepared, which solved the problem of insufficient performance in the high-temperature molding process of traditional mold release cloth, and achieved efficient mold release effect in the range of 260 to 400℃.

CN119615632APending Publication Date: 2025-03-14JIANGSU AIHE COMPOSITE MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411819390.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the existing composite material forming process, the traditional mold release fabric cannot meet the performance requirements during the high-temperature forming process, and the melting point of the tetrafluoro mold release fabric is only 317℃, which cannot meet the high-temperature forming needs of 260-400℃.

Method used

By modifying the surface of the glass fiber with silicone release agent or non-silicon release agent, a modified glass fiber material that is resistant to high temperature of 400°C is prepared for use as a mold release cloth. The material includes glass fibers and a release coating coated on the surface of the glass fibers, which is prepared from a silicone release agent or a non-silicon release agent of a specific composition.

Benefits of technology

The modified glass fiber material can effectively demold at a high temperature of 400°C. It is easy to remove from the surface of the composite material product after use, and leaves glass fiber patterns on the surface of the product, reducing the product's post-treatment time and improving process efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615632A_ABST
    Figure CN119615632A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite materials, and particularly relates to a modified glass fiber material, a preparation method thereof and application of the modified glass fiber material as demolding cloth. According to the invention, the glass fiber is used as a base material, the surface of the glass fiber is modified through the organic silicon release agent or the non-silicon release agent, the obtained modified glass fiber material is provided with the release coating, the surface coating is uniform, and the surface is provided with lines, so that the glass fiber which cannot be used as demolding cloth originally can play a demolding effect at a high temperature of 400 DEG C; after being used, the glass fiber is easily removed from the surface of a composite product, and glass fiber lines are reserved on the surface of the product, so that the post-treatment time of the product is shortened. The invention also provides application of the modified glass fiber material obtained by the scheme or the modified glass fiber material obtained by the preparation method as demolding cloth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a modified glass fiber material and a preparation method thereof and an application thereof as a demoulding cloth. Background Art

[0002] At present, the main molding processes for composite materials are oven molding and autoclave molding. During the implementation of these two processes, release cloth is needed to isolate the resin from other auxiliary materials. After the resin is solidified and formed, the release cloth is removed to obtain a composite material product.

[0003] With the rapid development of BMI resin prepregs and thermoplastic prepregs such as PEEK and PI, the molding temperature of composite materials has risen from the traditional 180℃ to 260-400℃. The melting points of the raw materials of traditional polyester and nylon release cloths are both below 260℃, which can no longer meet the performance requirements of high-temperature molding. Although the existing PTFE release cloth has a good demoulding effect, its melting point is only 317℃. Summary of the invention

[0004] The purpose of the present invention is to provide a modified glass fiber material and a preparation method thereof and an application of the modified glass fiber material as a demoulding cloth. The modified glass fiber material provided by the present invention is resistant to a high temperature of 400°C.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The invention provides a modified glass fiber material, comprising glass fiber and a release coating coated on the surface of the glass fiber; the release coating is prepared from an organic silicon release agent or a non-silicon release agent; the organic silicon release agent comprises the following components in parts by weight: 5 to 15 parts of decamethylcyclopentasiloxane, 10 to 30 parts of methylphenylvinyl polysiloxane, 0 to 3 parts of octavinyl-POSS, 0.5 to 5 parts of an anchoring agent, 0.5 to 5 parts of a platinum catalyst, 0.1 to 0.5 parts of an inhibitor and 100 to 500 parts of toluene; the non-silicon release agent comprises polyethyleneimine octadecyl urea and toluene.

[0007] Preferably, the weight of the release coating is 0.1 to 10 g / m 2 .

[0008] Preferably, the glass fiber includes one of glass fiber 1080, glass fiber 2116, glass fiber 2165, glass fiber 3313, glass fiber 7628 and glass fiber 7638.

[0009] Preferably, the viscosity of the methylphenylvinyl polysiloxane at 25° C. is 10,000 to 500,000 mPa·s, and the phenyl content is 10 to 30%.

[0010] Preferably, the platinum catalyst is a chloroplatinic acid-isopropanol mixture; the concentration of chloroplatinic acid in the chloroplatinic acid-isopropanol mixture is 5000-20000 ppm.

[0011] Preferably, the mass concentration of polyethyleneimine octadecyl urea in the non-silicone release agent is 0.5-1%.

[0012] The present invention also provides a method for preparing the modified glass fiber material described in the above scheme, comprising the following steps:

[0013] The modified glass fiber material is obtained by coating an organic silicon release agent or a non-silicon release agent on the surface of the glass fiber, drying it, and then curing it.

[0014] Preferably, the coating is performed by dipping, and the dipping time is 5 to 30 seconds.

[0015] Preferably, the curing temperature is 150-200° C., and the heat preservation curing time is 30-90 seconds.

[0016] The present invention also provides the use of the modified glass fiber material described in the above scheme or the modified glass fiber material obtained by the preparation method described in the above scheme as a release cloth.

[0017] The present invention provides a modified glass fiber material. The present invention uses glass fiber as a basic material, and uses an organic silicon release agent or a non-silicon release agent to modify the surface of the glass fiber. The obtained modified glass fiber material has a release coating, and the surface coating is uniform and has textures on the surface, so that the glass fiber that was originally unable to be used as a release cloth can have a demoulding effect at a high temperature of 400°C, and is easy to remove from the surface of a composite material product after use, and the texture of the glass fiber is left on the surface of the product, thereby reducing the time for post-processing of the product.

[0018] The present invention also provides a method for preparing the modified glass fiber material of the above scheme. The preparation method provided by the present invention has readily available raw materials, simple steps, and is easy to implement. At the same time, the coating content of the modified glass fiber material can be adjusted by controlling the dipping time, ensuring that it is easy to remove from the surface of the composite material product after use, and leaving the texture of the fiber cloth on the surface of the product.

[0019] The present invention also provides the use of the modified glass fiber material described in the above scheme or the modified glass fiber material obtained by the preparation method described in the above scheme as a demoulding cloth. The modified glass fiber material provided by the present invention can achieve a demoulding effect at a high temperature of 400°C, and can be easily removed from the surface of the composite material product after use as a demoulding cloth. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 The scanning electron microscope images of the glass fiber cloth and the modified glass fiber materials of Examples 1 and 4;

[0022] Figure 2 Graphs of water drop contact angles of glass fiber cloth, and modified glass fiber materials of Examples 1 and 5;

[0023] Figure 3 The photoelectron spectra of the glass fiber cloth and the modified glass fiber materials of Examples 2 and 5;

[0024] Figure 4 It is a practical application diagram of the modified glass fiber material autoclave of Examples 1-2 and Examples 4-5;

[0025] Figure 5 This is the thermal weight loss diagram of the modified glass fiber material of Examples 3 to 4. DETAILED DESCRIPTION

[0026] The invention provides a modified glass fiber material, comprising glass fiber and a release coating coated on the surface of the glass fiber; the release coating is prepared from an organic silicon release agent or a non-silicon release agent.

[0027] The modified glass fiber material provided by the present invention includes glass fiber; the glass fiber preferably includes one of glass fiber 1080, glass fiber 2116, glass fiber 2165, glass fiber 3313, glass fiber 7628 and glass fiber 7638.

[0028] In the present invention, the glass fiber is preferably temperature-resistant at 1000° C. or above.

[0029] The modified glass fiber material provided by the present invention comprises a release coating; the weight of the release coating is preferably 0.1 to 10 g / m 2 , specifically 0.1g / m 2 , 0.5g / m 2 , 1g / m 2 , 3g / m 2 , 5g / m 2 , 7g / m 2 , 9g / m 2 or 10g / m 2 .

[0030] In the present invention, the silicone release agent preferably includes the following components in parts by mass: 5 to 15 parts of decamethylcyclopentasiloxane (D5), 10 to 30 parts of methylphenylvinyl polysiloxane, 0 to 3 parts of octavinyl-POSS, 0.5 to 5 parts of anchoring agent, 0.5 to 5 parts of platinum catalyst, 0.1 to 0.5 parts of inhibitor and 100 to 500 parts of toluene.

[0031] In the present invention, the silicone release agent preferably includes 5 to 15 parts of decamethylcyclopentasiloxane (D5), specifically 7 parts, 9 parts, 11 parts or 13 parts.

[0032] In the present invention, the silicone release agent preferably includes 10 to 30 parts of methylphenylvinylpolysiloxane, and specifically may be 12 parts, 15 parts, 18 parts, 21 parts, 24 parts, 27 parts or 30 parts.

[0033] In the present invention, the viscosity of the methylphenyl vinyl polysiloxane at 25°C is preferably 10,000 to 500,000 mPa·s, specifically 10,000 mPa·s, 50,000 mPa·s, 100,000 mPa·s, 150,000 mPa·s, 200,000 mPa·s, 300,000 mPa·s, 400,000 mPa·s or 500,000 mPa·s, and the phenyl content is preferably 10 to 30%, specifically 10%, 15%, 20%, 25% or 30%.

[0034] In the present invention, the organosilicon release agent preferably includes 0 to 3 parts of octavinyl-POSS, specifically 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts or 3 parts.

[0035] In the present invention, the silicone release agent preferably includes 0.5 to 5 parts of an anchoring agent, specifically 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 3 parts, 4 parts or 4.5 parts.

[0036] In the present invention, the anchoring agent is preferably γ-glycidyloxypropyltrimethoxysilane.

[0037] In the present invention, the organosilicon release agent preferably includes 0.5 to 5 parts of a platinum catalyst, specifically 0.8 parts, 1 part, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts.

[0038] In the present invention, the platinum catalyst is preferably a chloroplatinic acid-isopropanol mixture; the concentration of chloroplatinic acid in the chloroplatinic acid-isopropanol mixture is preferably 5000-20000 ppm, specifically 5000 ppm, 10000 ppm, 15000 ppm or 20000 ppm.

[0039] In the present invention, the organosilicon release agent preferably includes 0.1 to 0.5 parts of the inhibitor, and specifically may be 0.2 parts, 0.3 parts or 0.4 parts.

[0040] In the present invention, the inhibitor is preferably 2-methyl-3-butyn-2-ol.

[0041] In the present invention, the organosilicon release agent preferably includes 100 to 500 parts of toluene, and specifically may be 150 parts, 200 parts, 250 parts, 300 parts, 350 parts, 400 parts or 450 parts.

[0042] In the present invention, the non-silicone release agent preferably includes polyethyleneimine octadecyl urea and toluene; the mass concentration of polyethyleneimine octadecyl urea in the non-silicone release agent is preferably 0.5-1%, specifically 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.

[0043] The present invention also provides a method for preparing the modified glass fiber material described in the above scheme, comprising the following steps:

[0044] The modified glass fiber material is obtained by coating an organic silicon release agent or a non-silicon release agent on the surface of the glass fiber, drying it, and then curing it.

[0045] In the present invention, the coating is preferably dip-coating; the dipping time is preferably 5 to 30 seconds, specifically 5 seconds, 10 seconds, 15 seconds, 20 seconds, 25 seconds or 30 seconds.

[0046] In the present invention, the drying temperature is preferably 50-70°C, specifically 50°C, 55°C, 60°C, 65°C or 70°C, and the heat preservation and drying time is preferably 1-3 minutes, specifically 1.5 minutes, 2 minutes or 2.5 minutes.

[0047] In the present invention, the curing temperature is preferably 150-200°C, specifically 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, and the heat preservation curing time is preferably 30-90s, specifically 30s, 40s, 50s, 60s, 70s, 80s or 90s.

[0048] In the present invention, the drying and curing equipment is preferably an oven.

[0049] The present invention also provides the use of the modified glass fiber material described in the above scheme or the modified glass fiber material obtained by the preparation method described in the above scheme as a release cloth.

[0050] The modified glass fiber material provided by the invention can achieve demoulding effect at a high temperature of 400° C. and can be easily removed from the surface of a composite material product after being used as a demoulding cloth.

[0051] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0052] Example 1

[0053] Add 10 parts of decamethylcyclopentasiloxane (D5), 15 parts of methylphenylvinylpolysiloxane, 0.5 parts of γ-glycidyloxypropyltrimethoxysilane, 0.1 parts of 2-methyl-3-butyn-2-ol and 300 parts of toluene into a container, stir evenly for 15 minutes, then add 1 part of chloroplatinic acid-isopropanol (10000ppm), stir for 5 minutes to obtain a silicone release agent glue solution.

[0054] Pour the silicone release agent into the glue tank, select the glass fiber cloth of model 2116, and dip it in the glue tank for 10 seconds, then transfer it to a 60°C drying section oven for drying for 1 minute, then transfer it to a 150°C curing section oven for curing for 60 seconds, and roll it up to obtain a modified glass fiber material.

[0055] Example 2

[0056] Add 10 parts of decamethylcyclopentasiloxane (D5), 15 parts of methylphenylvinylpolysiloxane, 0.5 parts of octavinyl-POSS, 0.5 parts of γ-glycidyloxypropyltrimethoxysilane, 0.1 parts of 2-methyl-3-butyn-2-ol and 300 parts of toluene into a container, stir evenly for 15 minutes, then add 1 part of chloroplatinic acid-isopropanol (10000ppm), stir for 5 minutes to obtain a silicone release agent glue solution.

[0057] Pour the silicone release agent into the glue tank, select the glass fiber cloth of model 2165, and dip it in the glue tank for 5 seconds, then transfer it to the 60℃ drying section oven for drying for 1 minute, then transfer it to the 180℃ curing section oven for curing for 60 seconds, and roll it up to obtain the modified glass fiber material.

[0058] Example 3

[0059] Add 5 parts of decamethylcyclopentasiloxane (D5), 20 parts of methylphenylvinylpolysiloxane, 0.5 parts of octavinyl-POSS, 0.5 parts of γ-glycidyloxypropyltrimethoxysilane, 0.1 parts of 2-methyl-3-butyn-2-ol and 300 parts of toluene into a container, stir evenly for 15 minutes, then add 1 part of chloroplatinic acid-isopropanol (10000ppm), stir for 5 minutes to obtain a silicone release agent glue solution.

[0060] Pour the silicone release agent into the glue tank, select the glass fiber cloth of model 7628, and dip it in the glue tank for 10 seconds, then transfer it to a 60°C drying section oven for drying for 1 minute, then transfer it to a 180°C curing section oven for curing for 60 seconds, and roll it up to obtain a modified glass fiber material.

[0061] Example 4

[0062] 1 part of polyethyleneimine octadecyl urea and 100 parts of toluene were added into a container and stirred evenly for 15 minutes to obtain a non-silicone release agent adhesive solution.

[0063] Pour the non-silicone release agent glue into the glue tank, select the glass fiber cloth of model 2165, and after dipping in the glue tank for 10 seconds, transfer it to a 60°C drying section oven for drying for 2 minutes, then transfer it to a 200°C curing section oven for curing for 30 seconds, and roll it up to obtain a modified glass fiber material.

[0064] Example 5

[0065] 1 part of polyethyleneimine octadecyl urea and 100 parts of toluene were added into a container and stirred evenly for 15 minutes to obtain a non-silicone release agent adhesive solution.

[0066] Pour the non-silicone release agent glue into the glue tank, select the glass fiber cloth of model 3313, and dip it in the glue tank for 20 seconds, then transfer it to a 60°C drying section oven for drying for 2 minutes, then transfer it to a 200°C curing section oven for curing for 30 seconds, and roll it up to obtain a modified glass fiber material.

[0067] Test Example 1

[0068] The modified glass fiber materials prepared in Examples 1 to 5 were tested for coating amount, release force, residual rate and 180° peeling force of bismaleimide resin prepreg. The release force test method was as follows: tesa TM The 7475 tape is attached to the release surface of the modified glass fiber material to be tested, and after being rolled back and forth three times with a 2kg pressure roller, a 25mm×130mm specimen is cut; the specimen is placed at room temperature for 20 minutes and then attached to a steel plate with adhesive. The 7475 tape is peeled off at an angle of 180° and a peeling speed of 300mm / min using a tensile testing machine. The reading of the tensile testing machine is the 20min release force.

[0069] The residual rate test method is: Standard tape NITTO TM31B is attached to the release surface to be tested, and rolled back and forth three times with a 2kg pressure roller, and a 25mm*300mm specification specimen is cut and made, and the specimen is placed horizontally between two glass plates; the glass plate is placed at 70℃, 50%RH, and 2kg pressure block pressure for 20h; after cooling at room temperature for 4h, the specimen is taken out; the 31B standard tape on the specimen is slowly peeled off from the modified glass fiber material and then attached to the steel plate, and a 2kg electric pressure roller is used to roll back and forth twice at a speed of 300mm / min under its own weight. After placing it for 20min, the tape is peeled off at a speed of 300mm / min on the tensile testing machine, and the average peeling force of the tensile testing machine reading is recorded as L1.

[0070] A new 31B standard tape (the same roll as the tape used for the sample strip) is directly attached to the steel plate, and rolled back and forth twice at a speed of 300mm / min under its own weight, and left for 20 minutes. The tape is peeled off at a speed of 300mm / min on the tensile machine, and the average peeling force of the tensile machine reading is recorded as L0. The residual rate is calculated as: L1 / L0×100%. The higher the residual rate, the better the performance of the modified glass fiber material, and the less effect it has on the viscosity of the sticky material attached to its surface.

[0071] The 180° peel test method refers to GB / T 2792-2014, and the results are shown in Table 1.

[0072] Table 1 Performance test results of modified glass fiber materials of Examples 1 to 5

[0073]

[0074] It can be seen from Table 1 that the surface coating of the modified glass fiber material prepared by the present invention is uniform, can achieve a demolding effect at a high temperature of 400°C, is easy to remove from the surface of the composite material product after use, and leaves glass fiber texture on the surface of the product, which reduces the time for post-processing of the product and improves the process efficiency.

[0075] Test Example 2

[0076] The glass fiber cloth, the modified glass fiber materials of Example 1 and Example 4 were subjected to scanning electron microscope analysis, and the results are as follows: Figure 1 As shown. Figure 1 It can be seen that glass fibers are very easy to separate into single filaments after cutting due to their coarse fibers and loose structure. After their surfaces are modified with silicone release agents or non-silicone release agents, the bonding force between the glass fibers is significantly enhanced, and they can maintain regular arrangement in the warp and weft directions and are not easy to fall apart after cutting.

[0077] The glass fiber cloth, the modified glass fiber materials of Example 1 and Example 5 were tested for water drop contact angle. The results are as follows: Figure 2 As shown. Figure 2It can be seen that after water is dripped on the surface of conventional glass fiber cloth, it shows a wetting effect; after being modified by silicone release coating, the water droplet contact angle on its surface increases to 130°; after being modified by non-silicone release coating, the water droplet contact angle on its surface reaches 125°, both of which have certain release properties.

[0078] Photoelectron spectroscopy analysis was performed on the glass fiber cloth and the modified glass fiber materials of Example 2 and Example 5. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that different coatings contain different surface elements. With the addition of the silicone coating, the Si content on the surface increases from 4.2% to 28% (Example 2), while the Si content in Example 5 is equivalent to that of the glass fiber cloth. Due to the introduction of the non-silicone release coating, the proportion of C on the surface increases from 51.5% to 72% relative to Example 2.

[0079] The modified glass fiber materials of Examples 1-2 and Examples 4-5 were respectively used in an autoclave, and the effects were as follows: Figure 4 As shown. Figure 4 It can be seen that the glass fiber cloth coated with silicone coating can be completely peeled off from the surface of the prepreg when used in an autoclave at 260°C, while the glass fiber cloth coated with non-silicone release coating can withstand a high temperature of 400°C, meeting the process requirements of existing thermoplastic prepregs. After use, the product did not experience abnormal conditions such as breakage and melting, and was easily peeled off from the surface of the product without problems such as tearing.

[0080] The modified glass fiber materials of Examples 3 to 4 were subjected to thermogravimetric analysis, and the results were as follows: Figure 5 As shown. Figure 5 It can be seen that Example 3 still retains 99% of its weight before 300°C, and after staying at 700°C for 10 minutes, the thermal weight loss is about 14%. Since Example 4 is a non-silicone release coating, its temperature resistance is higher than that of the silicone release coating. After reaching 700°C and staying for 10 minutes, its weight remains unchanged, and it has excellent heat resistance.

[0081] It can be seen from the above embodiments that the modified glass fiber material provided by the present invention can achieve a demoulding effect at a high temperature of 400° C., has a certain release property, and is easy to be removed from the surface of the composite material product after use.

[0082] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A modified glass fiber material, characterized in that: It includes glass fiber and a release coating coated on the surface of the glass fiber; The release coating is prepared from an organic silicon release agent or a non-silicon release agent; The organosilicon release agent comprises the following components in parts by weight: 5 to 15 parts of decamethylcyclopentasiloxane, 10 to 30 parts of methylphenylvinyl polysiloxane, 0 to 3 parts of octavinyl-POSS, 0.5 to 5 parts of anchoring agent, 0.5 to 5 parts of platinum catalyst, 0.1 to 0.5 parts of inhibitor and 100 to 500 parts of toluene; The non-silicone release agent includes polyethyleneimine octadecyl urea and toluene.

2. The modified glass fiber material according to claim 1, characterized in that: The weight of the release coating is 0.1 to 10 g / m 2 .

3. The modified glass fiber material according to claim 1, characterized in that: The glass fiber includes one of glass fiber 1080 , glass fiber 2116 , glass fiber 2165 , glass fiber 3313 , glass fiber 7628 , and glass fiber 7638 .

4. The modified glass fiber material according to claim 1 or 3, characterized in that: The methylphenylvinyl polysiloxane has a viscosity of 10000 to 500000 mPa·s at 25° C. and a phenyl content of 10 to 30%.

5. The modified glass fiber material according to claim 1, characterized in that: The platinum catalyst is a chloroplatinic acid-isopropanol mixture; the concentration of chloroplatinic acid in the chloroplatinic acid-isopropanol mixture is 5000-20000 ppm.

6. The modified glass fiber material according to claim 1, characterized in that: The mass concentration of polyethyleneimine octadecyl urea in the non-silicone release agent is 0.5-1%.

7. The method for preparing the modified glass fiber material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The modified glass fiber material is obtained by coating an organic silicon release agent or a non-silicon release agent on the surface of the glass fiber, drying it, and then curing it.

8. The preparation method according to claim 7, characterized in that: The coating is performed by dipping, and the dipping time is 5 to 30 seconds.

9. The preparation method according to claim 7 or 8, characterized in that: The curing temperature is 150-200° C., and the heat preservation curing time is 30-90 seconds.

10. Use of the modified glass fiber material according to any one of claims 1 to 6 or the modified glass fiber material obtained by the preparation method according to any one of claims 7 to 9 as a release cloth.